Armeria x carnotana (Plumbaginaceae) nothosp. nov. para el noroeste ibérico. Armeria x carnotana (Plumbaginaceae) nothosp. nov. for north-western Iberian Peninsula - Blanco-Dios, Jaime B. (Acta Botanica Malacitana, 2012)
Armeria x carnotana (Plumbaginaceae) nothosp. nov. for north-western Iberian Peninsula. Palabras clave. Armeria, Plumbaginaceae, híbrido, Galicia, España. Key words. Armeria, Plumbaginaceae, hybrid, Galicia, Spain